Comparability within Computer-Based Assessment: Does Screen Size Matter?. Issue 4 (2nd November 2018) - Chen, Jie; Perie, Marianne
Abstract: Due to increased use of computer-based assessments, comparability studies are moving beyond paper-and-pencil versus computer-based assessments to analyze variances with computers. It is therefore practically important to determine whether screen size and definition of the device affect students' performance. Using data from a large school district giving tests on either Macs with large, high-definition screens or Chromebooks with standard 14-inch screens, this study compared assessment results between devices by grade, subject, and item type. Results showed no significant evidence supporting a large and high-definition screen's positive impact on students' performance. Likewise, there was no relationship between the impact of screen size and grade level as well as item types. Limitations and future studies were discussed.